Material Flow Cost Accounting Approach for Sustainable Supply Chain Management System - Rochman Marota; Hamzah Ritchi; Uswatun Khasanah; Rizky Fisa Abadi (International Journal of Supply Chain Management, 2017)
The purpose of this paper is to examine whether material flow cost accounting (MFCA) can help generate innovation in supply chain management while playing its essential role. Full descriptive studies for reducing material losses through as described in this paper was employed to inspect whether MFCA approach would achieve reduction in material losses among multiple suppliers through efforts by the buyer. Both MFCA and supply chain management are strategic competitive tools for companies that solve logistical problems as a strategy to win the global competition. There is collaboration between MFCA approach and supply chain management as an integrated system. The constraints of combining supply chain management system with MFCA approach are technological developments and capabilities, environmental issues, global business competition, and the different point of view related to choice for responsive or efficient in business strategy. KeywordsMFCA, supply chain management, strategic competitive tools, integrated system, business strategy